Enhancing Propylene Glycol Product Yield by Modifying the Glycerol Hydrogenation Process - Syahidah, Aisyah Sabrina Nurul; Vania, Marsha; Aulia, Najmanisa; Hidayah, Nurul; Varado, Isaac (UPT Laboratorium Terpadu, Universitas Diponegoro, 2024)
The production of propylene glycol from glycerol is an emerging and sustainable approach in the chemical industry that can be considered completely renewable. Glycerol, a byproduct of biodiesel production, has gained attention as an alternative feedstock for the synthesis of value-added chemicals such as propylene glycol. This paper evaluates how to perform process modification for optimization of propylene glycol product yield. The process modification was carried out by adding compressor unit before entering a heater, adding heater unit before entering a mixer, and adding 2 separator unit before entering a distillation column. By modifying the addition of compressor unit, heater unit, and 2 separator unit, it has been proven that it can optimizing the propylene glycol product yield by up to 99.75%. Copyright © 2024 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).